1993
DOI: 10.5558/tfc69331-3
|View full text |Cite
|
Sign up to set email alerts
|

Acid scarification and hot water soaking of Racosperma auriculiforme seeds

Abstract: Nine methods of overcoming seed-coat dormancy of Racosperma auriculifotme (provenance KZNO) from Zaire were investigated. Soaking seeds in concentrated sulphuric acid for 15 or 30 min and then rinsing for 15 min with tap water produced the best results for laboratory testing as well as operational application. Boiling water from which the heat source has been removed and in which the seeds are placed and soaked until the water is cool (12-24 h) is the most suitable and economical method for social forestry pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Other recordings of gradual germination after HW or BW treatments in the Caesalpinioideae and Mimosoideae have been made by Clemens et al (1977), Tran (1979;A. sophorae), Odoemena (1988), Burrows (1991), Khasa (1993) and Burrows et al (2009). In contrast, other studies have shown rapid imbibition after HW or BW treatments, e.g.…”
Section: Imbibition -Hw-treated Seedsmentioning
confidence: 99%
“…Other recordings of gradual germination after HW or BW treatments in the Caesalpinioideae and Mimosoideae have been made by Clemens et al (1977), Tran (1979;A. sophorae), Odoemena (1988), Burrows (1991), Khasa (1993) and Burrows et al (2009). In contrast, other studies have shown rapid imbibition after HW or BW treatments, e.g.…”
Section: Imbibition -Hw-treated Seedsmentioning
confidence: 99%
“…Indeed, apart from his own publications (Pedley 1987a(Pedley -d, 1988) there appear to be few others that have adopted the name Racosperma. The only papers known to us are Khasa (1993), Khasa & Bousquet (1994) and (1995), Khasa et al (1994aKhasa et al ( ), (1994bKhasa et al ( ), (1995a and (1995b), Quoirin et al (1997), Carvalho et al (1999) and Takemori et al (2000). These are outweighed, many times over (far too many to list here), by papers adopting the name Acacia, including many in which the Racosperma combinations are cited in synonymy.…”
Section: Reaction To Pedley's Division Of Acaciamentioning
confidence: 97%
“…Surface-scarified and surface-sterilized seeds were germinated in the dark at 28 °C for 48 h in Petri dishes containing soft agar (1%). The duration of seed scarification in concentrated sulfuric acid (H 2 SO 4 ) and rinsing with tap water was 10 and 15 min, respectively (Khasa, 1993).…”
Section: Seedling Preparationmentioning
confidence: 99%